EGF‐R and PDGF‐R, but not bcl‐2, overexpression predict overall survival in patients with low‐grade astrocytomas - Varela, Mirta (2004)
Background and Objectives: Therapy of malignant glioma tumors is based on histology and clinical factors. However, comparable lesions may correspond with important prognostic differences. Our purpose was to analyze retrospectively the prognostic input of platelet-derived growth factor receptor (PDGF-R), epidermal growth factor (EGF-R), and bcl-2 expression in 103 malignant gliomas from uniformly treated patients. Methods: The expression of the antigens was analyzed by immunohistochemistry (IHC). Prognostic evaluation was performed with the multivariate proportional hazards model. The follow-up period lasted 19 (5–122) months for survivors. Results: We observed that almost 50% of gliomas showed high expression of PDGFR, while a lower expression of EGF-R and bcl-2 was found. No association between the main prognostic factors in malignant glioma (sex, age, histological grade, and Karnofsky score) and the labeling index (LI) of these antigens was observed. We found that only PDGF-R and EGF-R overexpression were associated with a shorter survival in patients with World Health Organization (WHO) II astrocytomas, being both associations independent of known prognostic factors, as shown by Cox model. Besides, we confirmed other authors’ results that high histological grade and low performance score were associated with worse prognosis. Conclusions: PDGF-R and EGF-R expression could be relevant in determining the prognosis of low-grade astrocytomas (LGAs) and in providing a more objective mechanism for their classification.